O’ZBEK TILIDA MUROJAATNING KOMUNIKATIV PRAGMATIK SHAKLLARI - Ernazarova Iroda Shavkat qizi; To’rayeva Maftuna Abdiraim qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article analyzes the communicative-pragmatic forms of address in the Uzbek language. Formal, informal, emotional and etiquette forms of address are shown on the basis of examples, and their socio-cultural and speech functions are indicated.